Relevansi Aliran Sosiological Jurisprudence terhadap Putusan Mahkamah Konsitusi Nomor 91/PUU.XVIII/2020 - Rahayu, Lulu Ulfie (AHKAM, 2022)
The truth is that the law cannot be separated from society as well as society cannot be separated from the law. In this millennial era, technology and communication are advancing as these changes have a positive and negative impact on the scope of society. Likewise with the law that is increasingly developing by bringing changes to all regulations that follow the development of the Legal community have very strong connections with social change, because the interaction of the legal field and social change are interconnected. Social change must coincide with legal norms, but other discontents of legal norms must be in accordance with existing social changes.